The hate u give - Thomas, Angie (Balzer + Bray, an imprint of HarperCollins Publishers, 2017)
After witnessing her friend's death at the hands of a police officer, Starr Carter's life is complicated when the police and a local drug lord try to intimidate her in an effort to learn what happened the night Kahlil died.